Mass Spectral Studies of Some 6-(2-N-Substituted aminothiazol-4-yl)chromones and Flavones - Prabha Sharma, Vinay; V. Singh, Om (Asian Journal of Chemistry, 2010)
Mass spectral studies of some 6-(2-N-substituted aminothiazol-4-yl) chromones and flavones are being presented in this paper which showed regular fragmentation patterns of chromones and thiazoles as well as other heterocyclic rings present in the molecule (e.g., morpholine).